2018
DOI: 10.1088/1361-6641/aaef02
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic determination of hole concentration inundopedGaAsBi

Abstract: Raman spectra of undoped GaAs 1−x Bi x (0<x<0.037) grown on GaAs by molecular beam epitaxy were investigated. With an increase of Bi component, we find that the longitudinal optical phonon-hole-plasmon-coupled (LOPC) mode first appears in the vicinity of the unscreened longitudinal optical (ULO) phonon frequency, and then shifts towards the transverse optical (TO) phonon frequency. A new vibrational mode (∼287 cm −1 ) between the TO and the ULO phonons was verified by use of low temperature polarized Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…To fit the experimental spectra in the −z(Y, Y)z configuration, we assumed the existence of a new vibrational mode at ∼286 cm −1 (denoted by an asterisk), which has been observed in GaAsBi alloys. 16,17,38) As discussed in Ref. 38, this mode can be attributed to the disordered activated mode or Fröhlich mode.…”
Section: Vibrational Propertiesmentioning
confidence: 84%
See 2 more Smart Citations
“…To fit the experimental spectra in the −z(Y, Y)z configuration, we assumed the existence of a new vibrational mode at ∼286 cm −1 (denoted by an asterisk), which has been observed in GaAsBi alloys. 16,17,38) As discussed in Ref. 38, this mode can be attributed to the disordered activated mode or Fröhlich mode.…”
Section: Vibrational Propertiesmentioning
confidence: 84%
“…Recently, Zhu et al estimated a lower native hole density in undoped GaAs 1−x Bi x (0% ⩽ x ⩽ 3.7%). 17) The calculated value increased from ∼6.5 × 10 16 to ∼2.8 × 10 17 cm −3 with increasing Bi composition. Moreover, they found that the hole density calculated using the LOPC mode increased monotonically with increasing excitation laser power.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…1. The intense peaks located at ~295 cm -1 and ~270 cm -1 are the unscreened longitudinal optical and transverse optical phonon modes of GaAs, respectively [17]. The spectrum exhibits several characteristic bands of the polyaniline (see inset in figure 1).…”
Section: Raman Measurementsmentioning
confidence: 98%
“…Depending on the laser power, the Raman spectra can have a significant contribution from photo-generated carriers [52][53][54][55][56][57][58], which can modify the LOPC modes due to intrinsic doping. Figure 4 shows typical Raman spectra of p-GaAs0.94Bi0.06 and n-GaAs samples, and in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 99%